Challenges of Research on Person-Centered Care in General Practice: A Scoping Review - Burgers, Jako S.; van der Weijden, Trudy; Bischoff, Erik W. M. A. (Frontiers in Medicine, 2021)
Background: Delivering person-centered care is one of the core values in general practice. Due to the complexity and multifaceted character of person-centered care, the effects of person-centered care cannot be easily underpinned with robust scientific evidence. In this scoping review we provide an overview of research on effects of person-centered care, exploring the concepts and definitions used, the type of interventions studied, the selected outcome measures, and its strengths and limitations. Methods: Systematic reviews on person-centered care compared to usual care were included from Pubmed, Embase, and PsycINFO. The search was conducted in February 2021. Data selection and charting was done by two reviewers. Results: The literature search yielded 481 articles. A total of 21 full-text articles were assessed for eligibility for inclusion. Four systematic reviews, published between 2012 and 2018, were finally included in this review. All reviews used different definitions and models and classified the interventions differently. The explicit distinction between interventions for providers and patients was made in two systematic reviews. The classification of outcomes also showed large differences, except patient satisfaction that was shared. All reviews described the results narratively. One review also pooled the results on some outcome measures. Most studies included in the reviews showed positive effects, in particular on process outcomes. Mixed results were found on patient satisfaction and clinical or health outcomes. All review authors acknowledged limitations due to lack of uniform definitions, and heterogeneity of interventions and outcomes measures. Discussion: Person-centered care is a concept that seems obvious and understandable in real life but is complex to operationalize in research. This scoping review reinforces the need to use mixed qualitative and quantitative methods in general practice research. For spreading and scaling up person-centered care, an implementation or complexity science approach could be used. Research could be personalized by defining therapeutic goals, interventions, and outcome variables based on individual preferences, goals, and values and not only on clinical and biological characteristics. Observational data and patient satisfaction surveys could be used to support quality improvement. Integrating research, education, and practice could strengthen the profession, building on the fundament of shared core values.